Tuning enantioselectivity in asymmetric hydrogenation of acetophenone and its derivatives via confinement effect over free-standing mesoporous palladium network catalysts - Wang, Y; Su, N; Ye, L; Ren, Y; Chen, X; Du, Y; Li, Z; Yue, B; Tsang, S; Chen, Q; He, H (2014)
The confinement effect on enantioselective hydrogenation of acetophenone and its derivatives over free-standing mesoporous Pd network catalysts was systematically studied. It was found for the first time that the enantiomeric excess (ee) could be effectively tuned by altering the confinement effect optimized by precise control of the topology, pore size, and lattice structure of mesoporous Pd catalysts. The double gyroid structure with proper pore size and desired lattice structure formed by KBH4 reduction provided suitable microenvironment to generate optimized confinement effect. The optimized catalyst exhibited ee of 40-73% at 273 K under atmospheric pressure of H2. DFT study revealed that the major enantiomeric product could be predicted by comparing relative energies of prochiral-R and -S complexes formed by acetophenone derivatives with S-proline. The energetically favored complex led to the formation of the corresponding enantiomer in excess upon hydrogenation, and ee was found to be linearly correlated with the energy difference between prochiral-R and -S complexes. © 2014 Elsevier Inc. All rights reserved.